Influence of Oxidation on Fracture Toughness of Carbon-Carbon Composites for High-Temperature Applications (Fracture and Structural Integrity, 2021)
Carbon-Carbon Composites (C-CC), used as composites for their remarkable qualities in the space industry as well as in many other industry sectors. C-CC has proven to be the most efficient material in extreme temperature situations. One of the best high-temperature materials with good thermal quality, such as high-temperature stability, outstanding thermal conductivity and low-temperature expansion coefficients. In aircraft, railways, trucks and even race vehicles, C-CC brake disks are in high demand. In comparison to the favorable thermal and mechanical qualities of C-CC, their great sensitivity to oxidation in an oxidizing environment at temperatures even around 400°C is a major restriction with these composites. In particular, a study of the C-CC oxidation mechanism helps to create protective measures for these composites. The present experimental study explores the influence of oxidation in static air on the fracture toughness of C-CC. At a temperature of around 400°C to 700°C in an increase of 100°C, an oxidation evaluation of the material was carried out in static air. Results show a decrease in fracture toughness to increase in the temperature. We can observe that C-CC fracture toughness is severely affected by oxidation. The variation began at 400°C from 6% and was anticipated at 700°C up to 45%.
Keywords: Carbon-Carbon Composites; Fracture Toughness; Oxidation; SENB Specimen; ASTM D5045